The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.7762/cnr.2014.3.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Diet Quality is Associated with Decreased Renal Function in Children with Chronic Kidney Disease

Abstract: Nutritional status of children with chronic kidney disease (CKD) is important since it affects growth and development. This study was to investigate overall diet quality measured by nutrient intake adequacy, nutrient density, and several dietary habits in children with CKD and its relationship with clinical parameters according to glomerular filtration rate (GFR). Assessment of nutritional status and diet quality was conducted in nineteen children with CKD. Average Z-scores of height, weight and body mass inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…These findings are in agreement with the Growth Failure in Children with Renal Disease (GFRD) study [ 24 ], where children with CKD achieved a Ca intake of 80% of normal requirements for age. Other studies have described similar or even lower Ca intakes [ 25 27 ], even from CKD stage 3 [ 28 ]. It is likely that a poor appetite also contributes to the reduced Ca intake in those with CKD.…”
Section: Discussionmentioning
confidence: 86%
“…These findings are in agreement with the Growth Failure in Children with Renal Disease (GFRD) study [ 24 ], where children with CKD achieved a Ca intake of 80% of normal requirements for age. Other studies have described similar or even lower Ca intakes [ 25 27 ], even from CKD stage 3 [ 28 ]. It is likely that a poor appetite also contributes to the reduced Ca intake in those with CKD.…”
Section: Discussionmentioning
confidence: 86%
“…A study conducted in Korea found that dietary habits and appetite status in children with CKD are associated with a decrease in kidney functions. In addition, the order of meals, frequency of main and break meals, having regular breakfast, excessive appetite and loss of appetite are recognized as determinants of diet quality (1). In this study, 87.5% of children with CKD have breakfast and dinner every day and skip the lunch.…”
Section: Resultsmentioning
confidence: 83%
“…In an extensive study of 5022 children conducted in North America, it was found that onethird of children with CKD had PEM and this rate was higher in the younger age group (7). The best known cause of PEM in chronic kidney disease is the inadequacy of nutrient storage of the body in response to an increase in nutritional requirements arising from rapid growth (1).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of children with CKD have indicated that diet quality and nutrient intake decrease as kidney function declines [4]. Anorexia and poor appetite are common in children with CKD and contribute to inadequate nutrient and caloric intake [5, 6].…”
Section: Introductionmentioning
confidence: 99%